A Comparative Study Of Parental Involvement On Students English Learning At Junior High School - Sartika, Diana; Yulmiati, Yulmiati; Khairi, M ikhsan (JUPE : Jurnal Pendidikan Mandala, 2023)
Parental involvement in English language learning plays an important role in shaping students' academic success and overall well-being. Based on pre-observation, it was found that many students still have difficulties in understanding English learning. This study was conducted with the aim to find out how parents' involvement and see the comparison of father and mother involvement in English learning by using qualitative method. There were 21 respondents and 6 parents who were purposively selected. The researcher collected data by distributing questionnaires to students and interviews with parents. We found that the involvement of both parents has a positive contribution to the progress of their children's English learning. The influence of father's involvement is not as strong as the influence of mother's involvement in English learning because fathers do not spend much time with their children at home because they are busy working. However, fathers also try to be a good example for their children. From the results above, it was found to maximize students' English learning, good cooperation and support between both parents is very necessary.